Dietary modulation of epigenetics: Implications for cancer prevention and progression - Si-Rui Zhu; Xin-Yu Liang; Qian Bai; Xiang-Min Ni; Jian Wang (Journal of Nutritional Oncology)
Abstract. Epidemiological studies indicate a strong correlation between various types of human cancer and dietary factors, whereas the specific mechanisms remain to be fully elucidated. Epigenetic alterations, such as DNA methylation, histone modifications, and noncoding RNA, are influenced by dietary components, especially phytochemicals and nutrients that participate in one-carbon metabolism. These alterations significantly impact cancer occurrence and progression. Consequently, epigenetic pathways may mediate the effects of diet on cancer risk. This review synthesizes the current information regarding the association of epigenetic alterations with cancer initiation and development, as well as the mechanisms by which diet exerts its influence on these changes. The goal of this minireview is to enhance the understanding of the roles of diet on epigenetic alterations to improve cancer prevention and treatment through diet.